An exploratory study on sri lankan mumpreneurs - Amitha, W.A.K.; Sewwandi, M.A.D. (University of Jaffna, 2020)
Entrepreneurship is playing a vital role in any economy today. The secret of being successful is the entrepreneurship for many of the developed countries in the world. Singapore is the best example. Moving forward from traditional entrepreneurship leads to find many of new branches of it. Motherhood and entrepreneurship are such a new arena in academia today. Scholars are highly concerning working mothers in their studies. However, the attention paid to the motherhood and entrepreneurship is deficient. This concept is a novel concept to the researchers and offers a vast array of benefits to any economy through women self-employment and caring babies. Hence, this study is dedicated to exploring the Mumprenurship in Sri Lankan context as an essential arena to study. The researchers executed an exploratory cross-sectional study by deploying the inductive approach to reveal mumpreneurs' challenges and motivational factors in Sri Lanka. Semi-structured interviews were conducted with mumpreneurs to collect required primary data based on the authors' semi-structured interview guide based on previous studies and hand-on experience of both the researchers. The findings of the study revealed specific motivational factors and some challenges encountered by Sri Lanka mumpreneurs. Further, these qualitative study findings are so worth for the current and potential mumpreneurs to understand the way forward as successful mumpreneurs while contributing to the social and economic spheres hugely. Also, policymakers and decision-makers of the economy can make viable decisions to boost this sub-sector of entrepreneurship since it gives lots of hidden benefits to the family, society and finally to the whole economy in many different ways. Future researchers can further study this valuable area by focusing on new methodologies and directions.
Keywords: Challenges; Entrepreneurship; Motivational factors and mumpreneurship